Vacation Benefits and Activities: Understanding Chinese Family Travelers. (March 2017) - Lehto, Xinran Y.; Fu, Xiaoxiao; Li, Hanliang; Zhou, Lingqiang
Family as a travel unit is an emerging phenomenon in China. This market segment, however, has not received as much scholarly attention as it deserves. This study investigated the vacation benefits that Chinese families pursue and their destination activity participation. Factor analysis revealed four dimensions of vacation benefits sought, namely, Communication and Togetherness, Shared Exploration, Escape and Relaxation, and Experiential Learning for Children. Taking pictures and videos was noted to be the most prevalent activity that Chinese family travelers were engaged in. This study further explored the interrelationships between the benefit-sought domains and destination activities. The results identified significant linkages between the two. The uncovered associations suggested that vacation activities served as a functional means to an end for Chinese families. Theoretical and managerial implications of the findings were discussed, followed by recommendations for future research.